Patterns of variation and covariation in the shapes of mandibular bones of juvenile salmonids in the genus Oncorhynchus. Issue 5 (15th September 2015) - Kimmel, Charles B.; Watson, Sawyer; Couture, Ryan B.; McKibben, Natasha S.; Nichols, James T.; Richardson, Shannon E.; Noakes, David L. G.
SUMMARY: What is the nature of evolutionary divergence of the jaw skeleton within the genus Oncorhynchus ? How can two associated bones evolve new shapes and still maintain functional integration? Here, we introduce and test a "concordance" hypothesis, in which an extraordinary matching of the evolutionary shape changes of the dentary and angular articular serves to preserve their fitting together. To test this hypothesis, we examined morphologies of the dentary and angular articular at parr (juvenile) stage, and at three levels of biological organization—between salmon and trout, between sister species within both salmon and trout, and among three types differing in life histories within one species, Oncorhynchus mykiss . The comparisons show bone shape divergences among the groups at each level; morphological divergence between salmon and trout is marked even at this relatively early life history stage. We observed substantial matching between the two mandibular bones in both pattern and amount of shape variation, and in shape covariation across species. These findings strongly support the concordance hypothesis, and reflect functional and/or developmental constraint on morphological evolution. We present evidence for developmental modularity within both bones. The locations of module boundaries were predicted from the patterns of evolutionary divergences, and for the dentary, at least, would appear to facilitate its functional association with the angular articular. The modularity results suggest that development has biased the course of evolution.